Deletion of Kaposi's sarcoma-associated herpesvirus FLICE inhibitory protein, vFLIP, from the viral genome compromises the activation of STAT1-responsive cellular genes and spindle cell formation in endothelial cells. - Stürzl, Michael; et al. (Journal of Virology, 2011)
Kaposi's sarcoma herpesvirus (KSHV) Fas-associated death domain (FADD)-like interleukin-1 beta-converting enzyme (FLICE)-inhibitory protein, vFLIP, has antiapoptotic properties, is a potent activator of the NF-κB pathway, and induces the formation of endothelial spindle cells, the hallmark of Kaposi's sarcoma, when overexpressed in primary endothelial cells. We used a reverse genetics approach to study several functions of KSHV vFLIP in the context of the whole viral genome. Deletion of the gene encoding vFLIP from a KSHV genome cloned in a bacterial artificial chromosome (BAC) reduced the ability of the virus to persist and induce spindle cell formation in primary human umbilical vein endothelial cells (HUVECs). Only a few, mainly interferon (IFN)-responsive, genes were expressed in wild-type KSHV (KSHV-wt)-infected endothelial cells at levels higher than those in KSHV-ΔFLIP-infected endothelial cells, in contrast to the plethora of cellular genes induced by overexpressed vFLIP. In keeping with this observation, vFLIP induces the phosphorylation of STAT1 and STAT2 in an NF-κB-dependent manner in endothelial cells. vFLIP-dependent phosphorylation of STAT1 and STAT2 could be demonstrated after endothelial cells were infected with KSHV-wt, KSHV-ΔFLIP, and a KSHV-vFLIP revertant virus. These findings document the impact of KSHV vFLIP on the transcriptome of primary endothelial cells during viral persistence and highlight the role of vFLIP in the activation of STAT1/STAT2 and STAT-responsive cellular genes by KSHV.